Application of universally amplifying plastid primers to environmental sampling of a stream periphyton community - Sherwood, A.R.; Chan, Y.L.; Presting, G.G.
To demonstrate the utility of universal plastid primers for probing of environmental samples, we extracted DNA from a tropical stream periphyton community and created two environmental clone libraries. We demonstrate the recovery of DNA sequences corresponding to the major groups of algae observed microscopically in the sample, illustrating the utility of these primers for analysis of environmental samples. Using a touchdown polymerase chain reaction technique, almost 99 percent of recovered sequences correspond to plastid-containing or cyanobacterial taxa, which allows algae to be targeted to the almost complete exclusion of noncyanobacterial prokaryotes and nonplastid-containing eukaryotes.
Keywords: 23S RRNA PLASTID MARKER; ALGAE; ENVIRONMENTAL SAMPLING; PERIPHYTON; STREAM; UNIVERSAL PRIMERS